Evaluation of international tourists’ satisfaction towards Bangladesh as a tourist destination - Biswas, Chhanda (2022)
This study aims to evaluate the influence of destination attributes on international tourists’ satisfaction within the context of Bangladesh. It also aims to investigate how their age and nationality affect their satisfaction levels. Using purposive sampling method, data collected from 387 international tourists were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) technique. The results of hypotheses testing confirmed that six destination attributes namely attraction, activity, amenity, accommodation, accessibility and safety had a significant positive influence on tourist satisfaction. Additionally, tourists’ age moderated the relationship between attraction, accommodation, safety and tourist satisfaction but did not moderate the relationship between activity, amenity, accessibility and tourist satisfaction. Furthermore, tourists’ nationality moderated the relationship between attraction, accessibility and tourist satisfaction but did not moderate the relationship between activity, amenity, accommodation, safety and tourist satisfaction. The novelty of this study is pioneering the integration of safety as an addition to the five destination attributes classified in the Holiday Satisfaction (HOLSAT) model. This study, therefore, adds to the existing literature by empirically extending HOLSAT destination attributes and explaining the moderating effects of tourists’ age and nationality on tourist satisfaction. It is suggested that further studies should extend the horizon by capturing the intention of international tourists to revisit and recommend Bangladesh as a tourist destination to others.